Comparison of the Efficacy of Ureteroscopy through a Flexible Vacuum-Assisted Ureteral Access Sheath with Tubeless-mini Percutaneous Nephrolithotomy for the Treatment of 3–2 cm Renal Calculi - Deng, Guanyun; Jiang, Kehua; Wang, Qing; Lu, Wenbing; Huang, Kunyuan; Sun, Fa (Urology Journal, 2025)
Purpose: To investigate the efficacy of the flexible vacuum-assisted ureteral access sheath (FV-UAS) combined with disposable flexible ureteroscope (FURS) versus tubeless-mini percutaneous nephrolithotomy (T-PCNL) in the treatment of renal calculi with a diameter of 2–3 cm. Materials and methods: This retrospective analysis included 270 patients with renal calculi with a maximum diameter of 2–3 cm treated between January 2022 and July 2024. Of these, 146 cases were treated with single-use ureteroscopic lithotripsy through an FV-UAS, while 124 cases were treated by tubeless PCNL (T-PCNL group) through a 16F Amplatz sheath. Perioperative indicators and postoperative stone-free rates (SFRs) were compared. Results: There was no significant difference in the stone-free rates (SFRs) between the two surgical methods. Using the criterion of a residual kidney stone diameter less than 4 mm, the SFRs at 3 days postoperatively were compared between the two groups: 95% confidence interval (CI), 0.56–2.28; odds ratio (OR) = 1.13; P = .724. The SFRs at 1 month postoperatively were: 95% CI, 0.417–2.60; OR = 1.041; P = .931. Using the criterion of a residual kidney stone diameter less than 2 mm, the SFRs at 3 days postoperatively were: 95% CI, 0.355–1.055; OR = 0.612; P = .076; the SFRs at 1 month postoperatively were: 95% CI, 0.374–1.320; OR = 0.703; P = .271. There was no significant difference in the incidence of systemic inflammatory response syndrome (SIRS) and the need for postoperative analgesia between the two groups (P = .813 and P = .839, respectively). The surgical duration in the FV-UAS group was significantly longer (P < .001). The decrease in postoperative hemoglobin (Hb) levels and hospital stay in the FV-UAS group were significantly lower than those in the T-PCNL group (both P < .001). Conclusion: For treating 2–3 cm renal calculi, both FV-UAS with disposable ureteroscope and 16F tubeless PCNL yield high stone-free rates. FV-UAS–assisted FURS reduces bleeding and hospital stay, whereas 16F tubeless PCNL shortens surgery duration.